A multifaceted view on the impacts of shrub encroachment. Issue 3 (July 2016) - Maestre, Fernando T.; Eldridge, David J.; Soliveres, Santiago
Abstract: Shrub encroachment, a global phenomenon with management implications, is examined in two papers in the current issue of Applied Vegetation Science . Barbosa da Silva et al. show that encroachment simplifies the herbaceous community, and Pittarello et al. illustrate how pastoral practices can restore encroached grasslands. While detrimental effects of shrub encroachment on grassland vegetation are often reported, we argue for a more holistic view when assessing this land‐cover change. Abstract : Shrub encroachment, a global phenomenon with management implications, is examined in two papers in the current issue of Applied Vegetation Science . Barbosa da Silva et al. show that encroachment simplifies herbaceous community, and Pittarello et al. illustrate how pastoral practices can restore encroached grasslands. While detrimental effects of shrub encroachment on grassland vegetation are often reported, we argue for a more holistic view when assessing this land cover change.